Tolerogenic dendritic cells pulsed with islet antigen induce long-term reduction in T-cell autoreactivity in type 1 diabetes patients - Nikolic, Tatjana; Suwandi, Jessica S.; Wesselius, Joris; Laban, Sandra; Joosten, Antoinette M.; Sonneveld, Petra; Mul, Dick; Aanstoot, Henk-Jan; Kaddis, John S.; Zwaginga, Jaap Jan; Roep, Bart O. (Frontiers in Immunology, 2022)
Restoration of immune tolerance may halt progression of autoimmune diseases. Tolerogenic dendritic cells (tolDC) inhibit antigen-specific proinflammatory T-cells, generate antigen-specific regulatory T-cells and promote IL-10 production in-vitro, providing an appealing immunotherapy to intervene in autoimmune disease progression. A placebo-controlled, dose escalation phase 1 clinical trial in nine adult patients with long-standing type 1 diabetes (T1D) demonstrated the safety and feasibility of two (prime-boost) vaccinations with tolDC pulsed with a proinsulin peptide. Immunoregulatory effects were monitored by antigen-specific T-cell assays and flow and mass cytometry. The tolDC vaccine induced a profound and durable decline in pre-existing autoimmune responses to the vaccine peptide up to 3 years after therapy and temporary decline in CD4 and CD8+ T-cell responses to other islet autoantigens. While major leukocyte subsets remained stable, ICOS+CCR4+TIGIT+ Tregs and CD103+ tissue-resident and CCR6+ effector memory CD4+ T-cells increased in response to the first tolDC injection, the latter declining thereafter below baseline levels. Our data identify immune correlates of mechanistic efficacy of intradermally injected tolDC diminishing autoimmunity in T1D.